On adult and larval morphology of Polydora cornuta Bosc, 1802 (Annelida: Spionidae) - Radashevsky, Vasily I. (Zootaxa, 2005)
The spionid mudworm Polydora cornuta Bosc, 1802 (formerly Polydora ligni Webster, 1880) is redescribed based on museum and new material collected in temperate and subtropical zones worldwide. Previously unobserved features are noted, including arrangement of lateral ciliated organs on all chaetigers but 4 and 5, metanephridial organs and glandular pouches beginning from chaetiger 7. Larval morphology is described and illustrated based on material from Brazil. The larvae are characterized by middorsal vesiculate melanophores from chaetiger 3 or 4, dorsal paired melanophores band-shaped from chaetiger 3 and ramified from chaetiger 7 or 8, large ramified yellow chromatophores on ventral side from chaetigers 5–7, specific modified chaetae in notopodia of chaetiger 5, and hooks in neuropodia from chaetiger 7 not accompanied by any other kind of chaetae. Some differences from earlier descriptions of larvae from Europe and North America are highlighted. Consistent morphological differences between adults from distantly separated populations, as suggested in earlier studies, were not revealed and all the examined materials are referred to one species.